2018
DOI: 10.1016/j.brainres.2018.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen exerts neuroprotective effects on OGD/R damaged neurons in rat hippocampal by protecting mitochondrial function via regulating mitophagy mediated by PINK1/Parkin signaling pathway

Abstract: Cerebral ischemia/reperfusion injury (IRI) is a serious complication during the treatment of stroke patients with very few effective clinical treatment. Hydrogen (H2) can protect mitochondria function and have favorable therapeutic effects on cerebral IRI. Mitophagy plays an important role in eliminating damaged or dysfunctional mitochondria and maintaining mitochondria homeostasis. However, whether the protection of H2 on cerebral IRI is via regulating mitophagy is still unknown. In this study, OGD/R damaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…f The expression of BNIP3, caspase-3, cleaved-caspase-3, caspase-9 and cleaved-caspase-9 in the modified HT22 cells was examined by WB. (*P < 0.05, **P < 0.01, versus mimic NC + Vector or Vector + si-Ctrl; # P < 0.05, ## P < 0.01, versus Vector + miR-182-5p mimic Vector + si-BNIP3) mitophagy has a crucial role in various diseases, such as CI/R injury [20], Parkinson's disease and septic acute kidney injury [21,22]. However, SNHG14 overexpression or knockdown had no effect on the expression of PINK1 and Parkin, suggesting that SNHG14 can not regulate mitophagy by activating PINK1/Parkin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…f The expression of BNIP3, caspase-3, cleaved-caspase-3, caspase-9 and cleaved-caspase-9 in the modified HT22 cells was examined by WB. (*P < 0.05, **P < 0.01, versus mimic NC + Vector or Vector + si-Ctrl; # P < 0.05, ## P < 0.01, versus Vector + miR-182-5p mimic Vector + si-BNIP3) mitophagy has a crucial role in various diseases, such as CI/R injury [20], Parkinson's disease and septic acute kidney injury [21,22]. However, SNHG14 overexpression or knockdown had no effect on the expression of PINK1 and Parkin, suggesting that SNHG14 can not regulate mitophagy by activating PINK1/Parkin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…There are accumulating data showing that mitophagy plays an important role in eliminating damaged or dysfunctional mitochondria and maintaining mitochondria homeostasis [ 39 ]. Mitochondria contain less cytochrome c and more pro-apoptotic protein Bax expression; it tends to swell, break, and have a lower membrane potential [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cerebral and cardiac ischemia injury, however, autophagy can be protective or destructive [ 20 , 21 ]._ENREF_17 For example, it has been reported that hydrogen, heat shock protein B8 (HSPB8) exert neuroprotective effects by protecting mitochondrial function via enhanced mitophagy in oxygen-glucose deprivation/reoxygenation-induced neuron damage in rat hippocampal [ 39 , 54 ]._ENREF_37 In contrast, it has been reported that knockout of programmed cell death 5 (PCD5) has a protective role in middle cerebral artery occlusion model by promoting apoptosis and autophagy through the activation of HIF-1α-BNIP3 signaling pathway [ 55 ]. This inconsistency is similar with cardiomyocyte.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the increased of ROS production can inhibit prolyl hydroxylase enzyme (PHD) activity, and prevent the degradation and enhance the stability of HIF-1 44 . However, excessive ROS may related to the cellular oxidative damage, such as mitochondrial dysfunction and mitophagy 45 . Hif-1aa improved ROS production and concomitant increase of mitochondrial membrane potential, suggesting that Hif-1aa maintains hyperpolarization of the mitochondrial membrane potential.…”
Section: Discussionmentioning
confidence: 99%